Relationship of the Brief UCSD Performance-based Skills Assessment (UPSA-B) to multiple indicators of functioning in people with schizophrenia and bipolar disorder - Mausbach, Brent T (2010)
OBJECTIVE: This study assessed the relationship between multiple indicators of ‘real-world’ functioning and scores on a brief performance-based measure of functional capacity known as the Brief University of California San Diego (UCSD) Performance-based Skills Assessment (UPSA-B) in a sample of 205 patients with either serious bipolar disorder (n = 89) or schizophrenia (n = 116). METHODS: Participants were administered the UPSA-B and assessed on the following functional domains: (i) independent living status (e.g., residing independently as head of household, living in residential care facility); (ii) informant reports of functioning (e.g., work skills, daily living skills); (iii) educational attainment and estimated premorbid IQ as measured by years of education and Wide Range Achievement Test reading scores, respectively; and (iv) employment. RESULTS: Better scores on the UPSA-B were associated with greater residential independence after controlling for age, diagnosis, and symptoms of psychopathology. Among both bipolar disorder and schizophrenia patients, higher UPSA-B scores were significantly related to better informant reports of functioning in daily living skills and work skills domains. Greater estimated premorbid IQ was associated with higher scores on the UPSA-B for both schizophrenia and bipolar disorder participants. Participants who were employed scored higher on the UPSA-B when controlling for age and diagnosis, but not when controlling for symptoms of psychopathology. CONCLUSIONS: These data suggest the UPSA-B may be useful for assessing capacity for functioning in a number of domains in both people diagnosed with schizophrenia and bipolar disorder.